On incentive compatible, individually rational public good provision mechanisms - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2018)
This paper characterizes mechanisms satisfying Bayesian incentive compatibility (BIC) and interim individual rationality (IIR) in the classical public good provision problem. Many papers in the literature obtain the results in the so-called standard model of ex ante identical agents with a continuous, closed interval of types. Although the standard model and more generally a continuum type space are widely used in the literature, it is nonetheless an abstraction of reality. Given that the public good provision problem has occupied a central application in the theory of mechanism design, we propose a "stress test" for the results in the standard model by subjecting them to a fi nite discretization over the standard model. The main contribution of this paper is that many of the known results gained within the standard continuum type space also hold when it is replaced by a discrete type space.